The Effect of Application of Payroll Accounting Information System in Increasing the Effectiveness of Company's Internal Control (Literature Study) - R. Dian Wirdiansyah; Agus Munandar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to understand the use of payroll accounting information systems in increasing the effectiveness of the company's internal control. The approach in this study uses a qualitative descriptive approach. The approach used in this research is to use a literature review approach. The results showed that from 10 previous studies there were 7 studies where the results stated that the payroll accounting information system had been running effectively and was able to increase the effectiveness of the company's internal control, and 3 other studies stated that the payroll accounting information system was not running effectively and had not been able to increase the effectiveness of company’s internal control.